2023
DOI: 10.3390/ijms24054747
|View full text |Cite
|
Sign up to set email alerts
|

Zebra-Sphinx: Modeling Sphingolipidoses in Zebrafish

Abstract: Sphingolipidoses are inborn errors of metabolism due to the pathogenic mutation of genes that encode for lysosomal enzymes, transporters, or enzyme cofactors that participate in the sphingolipid catabolism. They represent a subgroup of lysosomal storage diseases characterized by the gradual lysosomal accumulation of the substrate(s) of the defective proteins. The clinical presentation of patients affected by sphingolipid storage disorders ranges from a mild progression for some juvenile- or adult-onset forms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 170 publications
0
2
0
Order By: Relevance
“…The teleost zebrafish ( Danio rerio ) represents a useful platform to model human genetic diseases. In addition, lipidomic studies performed in zebrafish have identified all the main classes of lipids present in mammals, supporting the possibility to model diseases of the lipidic metabolism in this animal species, including sphingolipidoses [7] .…”
Section: Introductionmentioning
confidence: 79%
“…The teleost zebrafish ( Danio rerio ) represents a useful platform to model human genetic diseases. In addition, lipidomic studies performed in zebrafish have identified all the main classes of lipids present in mammals, supporting the possibility to model diseases of the lipidic metabolism in this animal species, including sphingolipidoses [7] .…”
Section: Introductionmentioning
confidence: 79%
“…However, mechanistic explorations in most zebrafish models of leukodystrophies have shown similarity to human physiopathology. For example, the biochemical pathways associated with peroxisomal β-oxidation or sphingolipid metabolism, critically affected in several leukodystrophies, have been shown to be conserved in zebrafish (Kamoshita et al, 2022;Mignani et al, 2023;Strachan et al, 2017) (Figure 2a).…”
Section: Challenges and Future Directionsmentioning
confidence: 99%